Streptococcus zooepidemicus Meningitis in an HIV-Positive Horse Breeder Patient: A Case Study and Literature Review - Petya Argirova; Yordan Kalchev; Ivan Baltadzhiev; Mariyana Stoycheva; Marianna Murdjeva (MDPI AG, 2023)
Streptococcus equi subsp. zooepidemicus is a rare etiologic agent of bacterial meningitis in humans. The disease is a zoonotic infection and is transmitted through close contact with domestic animals, mainly horses. Only 37 cases of Streptococcus zooepidemicus meningitis have been reported in the literature until July 2023. The aim of this study is to present a rare clinical case of S. zooepidemicus-related meningitis in a human immunodeficiency virus (HIV)-positive patient and analyze the literature. We present a 23-year-old horse breeder patient with advanced immunosuppression due to acquired immunodeficiency syndrome (AIDS) and S. zooepidemicus meningitis, admitted at the Clinic of Infectious Diseases, St. George University Hospital, Plovdiv. The course of meningitis was severe since the beginning, with significant cerebral edema, disturbances in consciousness, persistent fever, and the development of complications against the background of AIDS-related conditions. S. zooepidemicus was microbiologically detected from cerebrospinal fluid culture. After prolonged treatment and a long hospital stay, the patient's condition improved, and eventually he was discharged and recovered from the acute neuroinfection. Although extremely rare, S. zooepidemicus should be considered in patients with clinical and laboratory evidence of bacterial meningitis who have contact with animals, especially horses, other domestic animals, and their dairy products, as well as in immunocompromised patients. To the best of our knowledge, the current clinical case is the first report of S. zooepidemicus-related meningitis in a patient with HIV/AIDS.